Air pollution, governance quality, and health outcomes: evidence from developing countries - Ahmad, Nor Asma; Ismail, Normaz Wana; Ahmad Sidique, Shaufique Fahmi; Mazlan, Nur Syazwani (Springer Science and Business Media Deutschland GmbH, 2023)
While studies have demonstrated that air pollution can be catastrophic to the populations health, few empirical studies are found in the economic literature because a considerable proportion of the evidence comes from epidemiological studies. Because of the crucial role of governance in the health community, good governance has been a contentious issue in public sector management in recent years. Therefore, the aim of this study is to examine the efects of air pollution and the role of governance on health outcomes. This study employed the generalized method of moment (GMM) estimation techniques to analyse panel data for 72 developing countries from 2010 to 2017. The empirical results confrm that higher PM2.5 and CO2 levels have a detrimental infuence on life expectancy and healthy life expectancy, whereas the role of governance has a positive impact on life expectancy and healthy life expectancy. Furthermore, the fndings show governance quality plays a role in moderating the negative efect of PM2.5 on health outcomes. The ongoing rise in air pollution has had a signifcant impact on the health of developing countries. It appears that governance quality has improved health outcomes. The fndings have important policy implications, such that strengthening governance can reduce air pollution emissions in developing countries. However, to reduce the health efects of air pollution, developing countries must implement efective environmental development policies and track the implementation and enforcement of such policies.